PP.LB02.26: PROSPECTIVE STUDY ON LIRAGLUTIDE EFFECT ON BLOOD PRESSURE, LIPIDS PROFILE AND LIVER ENZYMES IN ARABS PATIENTS WITH TYPE 2 DIABETES MELLITUS. ANALYSIS FROM LEAD-ARAB STUDY. (June 2015) - Abdelgadir, E.; Bashier, A.; Altinay, A.; Abdalla, M.; Abusnana, S.; Alawadi, F.; Elsayed, M.; Makeen, S.
Abstract : Objective: We aimed to assess the changes in Blood pressure, Lipids profile, and Liver function test from the day of starting the Liraglutide and after 6 months of therapy. We wanted to assess the same blood pressure and metabolic changes in insulin and non-insulin treated subjects before and after initiation of the Liraglutide and after 6 months. Figure. No caption available. Design and method: This was a prospective study that included patients who were eligible to start Liraglutide. We took consent, reported BMI and withdrew the baseline tests at the first visit. We replicated those tests at 3 and 6 months respectively; we measured weight, blood pressure. Creatinine, lipid profile, AST and ALT were recorded, as well as Insulin doses. Patients who did not complete the 6 months duration or who missed the follow-up and patients with contradicting results in medical files and the electronic database were excluded from the study. Results: 365 patients signed the consent. From a baseline weight of 96.01 ± 19.2 Kilograms, the weight loss was higher in the insulin treated group 96 + 3 to 93 + 5 VS 93 + 5 to 98 + 3.5, P = 0.02. There was a highly significant improvement in total cholesterol and triglycerides at 6 months after initiation of Liraglutide. There was no significant change in systolic blood pressure. But worth mentioning, the average diastolic blood pressure improved remarkably (74.4 ± 10 to 72 ± 9 mmHg at 6 months P < 0.001). Interestingly, those who were used to take insulin along with Liraglutide had significantly lower average diastolic BP at both start and the end of the study duration; 73 + 4 VS 76 + 4 P = 0.05, and (71 + 5 VS 73 + 4.6) p = 0.02, respectively. ALT and AST readings were significantly lowered (P = 0.0000) even thought they were within normal range at the start. Conclusions: Our study Liraglutide showed remarkable improvement in weight, HbA1c, Liver enzymes, diastolic blood pressure, When it was added to multiple oral hypoglycemic agents, with or without insulin, in patients with type 2 diabetes. Nonetheless, Combination of Liraglutide and Insulin gave better diastolic blood pressure outcomes.